Hello lighthouse - Blackall, Sophie (New York : Little, Brown and Company, 2018)
Explores the life of one lighthouse as it beams its message out to sea through shifting seasons, changeable weather, and the tenure of its final keeper.
Includes one fold-out page.
School Library Journal starred, January 2018
Booklist starred, February 2018
Bulletin of the Center for Children's Books starre, April 2018
Pub Weekly, January 2018
Kirkus Starred, February 2018
Keywords: Lighthouses -- Fiction